2008
DOI: 10.1007/s10530-008-9315-1
|View full text |Cite
|
Sign up to set email alerts
|

Tree leaf litter composition and nonnative earthworms influence plant invasion in experimental forest floor mesocosms

Abstract: Dominant tree species influence community and ecosystem components through the quantity and quality of their litter. Effects of litter may be modified by activity of ecosystem engineers such as earthworms. We examined the interacting effects of forest litter type and earthworm presence on invasibility of plants into forest floor environments using a greenhouse mesocosm experiment. We crossed five litter treatments mimicking historic and predicted changes in dominant tree composition with a treatment of either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…These results are in line with observations made in previous studies which showed that plant species influence soil organisms through the quantity and the quality of their litter (Gonzàlez and Zou 1999;Belote and Jones 2009;Norgrove et al 2009). In both trials, the density of earthworms was responsive to the introduction of legumes, particularly the detritivores (name- ly D. saliens and D. baeri) and polyhumics (such as S. zielae).…”
Section: Earthworm Diversity and Abundancesupporting
confidence: 93%
See 3 more Smart Citations
“…These results are in line with observations made in previous studies which showed that plant species influence soil organisms through the quantity and the quality of their litter (Gonzàlez and Zou 1999;Belote and Jones 2009;Norgrove et al 2009). In both trials, the density of earthworms was responsive to the introduction of legumes, particularly the detritivores (name- ly D. saliens and D. baeri) and polyhumics (such as S. zielae).…”
Section: Earthworm Diversity and Abundancesupporting
confidence: 93%
“…Based upon the classification made by Jamaludheen and Kumar (1999) and considering N contents in litters of this study, leaf litter from L. purpureus and C. odorata can be considered as N rich (N>15 mg g −1 ) while that of C. cajan was fairly N rich (10 mg g −1 <N<15 mg g −1 ) and that from the savanna, N poor (N<0.10 mg g −1 ). These N content levels have great influence on soil biological activity and nutrient cycling (Tian et al 1993;Belote and Jones 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most dramatic changes have been documented in island ecosystems such as those on Hawaii (Waring et al 1993 ) and New Zealand dependence are the most robust against disturbances promoting extinctions (Ollerton et al 2003 ), such results suggest that the invasive species and its mutualists might be more resistant to disturbances, which would increase the probability of permanence and survival of such invasive in the network. This, added to a preferential interaction among invasive species, might lead to invasional meltdown, precipitating an even higher impact of the invasion on the native community, similar to those reported for other systems and interactions (see, for example, Grosholz 2005 ;Griffen et al 2008 ;Belote & Jones 2009 ).…”
Section: The Dynamics Of Disruptionsupporting
confidence: 67%